If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(64.5*x)/6-((3*x)/4) = x-11 // - x-11
(64.5*x)/6-((3*x)/4)-x+11 = 0
(64.5*x)/6+(-3/4)*x-x+11 = 0
9*x+11 = 0 // - 11
9*x = -11 // : 9
x = -11/9
x = -11/9
| q-p=6 | | 2x-4=5+6x | | (Y)=7 | | 9p+3q=-2 | | 3z+6(z+3)-10= | | 4y+4y=-16 | | F(4z)=3x^2+4 | | X+2X+2=4 | | h=1.5+8.4t+-4.9t^2 | | 6y-3(y+4)+3(y-6)= | | 4*3/10 | | 3(4a-8)+12= | | 8x+4(-2X+1)=-4 | | 22=8X-3 | | -(3/2)X=4/7 | | 16x+11x+16y-20y+6-10= | | 24=18-2q | | 24=18-29 | | x=1.2+0.6x | | -38=3(y-6)-5y | | 4x-3/2=-3/2x-6/5 | | -5-X/-3=-5 | | -8(5-3x)=2(x+11) | | s^2+4s+16=0 | | 3x+4+3x+3x+3=180 | | 6y+2=-2 | | (m^2)*x+1=m*x+m | | 5y-8=-38 | | Graphx=-1+-0.3333 | | 12X-3X+516=5+5X+15 | | 25=y-7 | | 8y-3=2(2y+8) |